Fundamental resonance in one generalized system of type Van der Pol - Dinh, Nguyen Van; Chi, Tran Kim (Vietnam Journal of Mechanics, 1996)
In the present paper, an oscillating system of type Vanderpol is considered. The fundamental resonance is examined, degenerated cases are analyzed in detail; singular points are used to distinguished various forms of the amplitude frequency curve.